POLA DAKWAH NAHDLATUL ULAMA DI KOTA BANJARMASIN - Fahmi Fahmi (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2015)
Nahdlatul Ulama (NU) is a big organization in Indonesia and it spreads to the entire areas in Indonesia from Aceh to Papua. In central area of Indonesia, precisely in Banjarmasin, NU can exists and recruits a lot of followers who are generally Pesantren-graduates, which are called